2020
DOI: 10.5964/jnc.v6i3.314
|View full text |Cite
|
Sign up to set email alerts
|

Iconicity in mathematical notation: Commutativity and symmetry

Abstract: Mathematical notation includes a vast array of signs. Most mathematical signs appear to be symbolic, in the sense that their meaning is arbitrarily related to their visual appearance. We explored the hypothesis that mathematical signs with iconic aspects – those which visually resemble in some way the concepts they represent – offer a cognitive advantage over those which are purely symbolic. An early formulation of this hypothesis was made by Christine Ladd in 1883 who suggested that symmetrical signs should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Intriguingly, the relationship between visual symmetry and abstract thought may extend to other forms of transformation invariance beyond the concepts tokened by predicates in natural language. A recent paper explored the relationship between the visual symmetry of mathematical symbols and the related mathematical concept of commutativity (i.e., where the order of operations is interchangeable, as for addition and multiplication; Wege et al, 2020). The authors found that participants have a strong tendency to associate vertically symmetrical symbols (e.g., ▲) with commutativity, as compared to when these same symbols are rotated 90 degrees (e.g., ▶), which is known to diminish the salience of visual symmetry (Wagemans, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the relationship between visual symmetry and abstract thought may extend to other forms of transformation invariance beyond the concepts tokened by predicates in natural language. A recent paper explored the relationship between the visual symmetry of mathematical symbols and the related mathematical concept of commutativity (i.e., where the order of operations is interchangeable, as for addition and multiplication; Wege et al, 2020). The authors found that participants have a strong tendency to associate vertically symmetrical symbols (e.g., ▲) with commutativity, as compared to when these same symbols are rotated 90 degrees (e.g., ▶), which is known to diminish the salience of visual symmetry (Wagemans, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…23 It is described as "the reversed initial letter of the word contains [contiene]" in [Peano 1889b, 6], 24 whereas the symbol or included, he notes that "this figurative notation is very convenient and fairly widespread" [Peano 1916[Peano -1917. That the use of iconic mathematical symbols has indeed cognitive advantages has recently been shown in [Wege, Batchelor et al 2020]. 23.…”
Section: Iconicity and Mnemonicsmentioning
confidence: 95%
“…Intriguingly, the relationship between visual symmetry and abstract thought may extend to other forms of transformation invariance beyond the concepts tokened by predicates in natural language. A recent paper explored the relationship between the visual symmetry of mathematical symbols and the related mathematical concept of commutativity (i.e., where order of operations is interchangeable, as for addition and multiplication) (Wege et al, 2020). The authors found that participants have a strong tendency to associate vertically symmetrical symbols (e.g., ▲) with commutativity, as compared to when these same symbols were rotated 90 degrees (e.g., ▶), which is known to diminish the salience of visual symmetry (Wagemans, 1997).…”
Section: Beyond Language and Vision: Symmetry In Mathematical Reasoningmentioning
confidence: 99%